Respon Galur Jagung Manis (Zea mays Var. saccharata Sturt) MS-UNSIKA Generasi M8 Terhadap Hama Ulat Grayak (Spodoptera frugiperda) di Dataran Rendah - Shadrina, Wahdani Nur; Syafii, Muhammad; Surjana, Tatang (JURNAL AGROPLASMA, 2024)
Seeds with superior quality can reduce the level of disease and pest attacks and can increase production yields. This research aims to determine differences in resistance of several lines of sweet corn (Zea Mays Var. saccharata Sturt) based on armyworm pest resistance. This research was carried out in one of the lands of Kalihurip Village, Cikampek District, Karawang Regency. The experiment will start from February 2024 to May 2024. The method used is experimental, using a single factor Randomized Block Design (RAK) consisting of 10 treatments and repeated 3 times, so that 30 experimental units are obtained. consisting of: SR1 (MS-UNSIKA- profilik), SR2 (SR-3 Sweet Boy F2), SR3 (SR-1 Latan), M6 (M6 gamma ray radiation dose 200 gy), M9 (M9 gamma ray radiation dose 200 gy ), M10 (M10 gamma ray radiation 200 gy), G11 (F2 mutant Talent variety), G12 (S1 Maestro variety), G13 (F2 Talent variety), G14 (F2 Bonanza variety). The experimental results will be tested using the F test, if there is a real effect then it will be tested further by the Duncan Multiple Range Test (DMRT) at 5% level. The results of the research showed that there was no real difference in the intensity of armyworm attacks on various lines of sweet corn plants in the treatment of various lines of sweet corn on the intensity of armyworm attacks. The Ms-Unsika strain showed the highest resistance, while Var. Maestro showed the highest susceptibility and there was no real correlation between disease and pest attacks on production results in the parent line of sweet corn (Zea mays Var. saccharata Sturt) MS-Unsika generation M8 mutant. Keywords: sweet corn parent lines, pests, crop yield